2020
DOI: 10.1111/jth.15103
|View full text |Cite
|
Sign up to set email alerts
|

Extreme thrombocytosis is associated with critical illness and young age, but not increased thrombotic risk, in hospitalized pediatric patients

Abstract: Background: Extreme thrombocytosis (EXT, platelet count > 1000 × 10 3 /μL) is an uncommon but potentially clinically significant finding. Primary EXT in the setting of myeloproliferative disorders is linked to thrombotic and/or bleeding complications more frequently than secondary EXT, which typically occurs in reaction to infection, inflammation, or iron deficiency. However, comorbidities have been reported in adults with secondary EXT. Clinical implications of EXT in children are not well defined, as prior s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
3
9
0
Order By: Relevance
“…33) However, reactive thrombocytosis, notably extreme thrombocytosis, in A c c e p t e d A r t i c l e newborn infants does not seem to be associated with an increased risk of hemorrhagic or thromboembolic complications. 24,26,28,29) Preterm infants with a gestational age < 32 weeks and thrombocytosis had a higher incidence of retinopathy of prematurity according to Del Rey Hurtado de Mendoza et al 4) Conversely, other studies reported that thrombocytopenia, not thrombocytosis, is a risk factor for retinopathy of prematurity. 34) Thus, the association between thrombocytosis and retinopathy of prematurity remains controversial.…”
Section: Complications Of Thrombocytosismentioning
confidence: 98%
See 1 more Smart Citation
“…33) However, reactive thrombocytosis, notably extreme thrombocytosis, in A c c e p t e d A r t i c l e newborn infants does not seem to be associated with an increased risk of hemorrhagic or thromboembolic complications. 24,26,28,29) Preterm infants with a gestational age < 32 weeks and thrombocytosis had a higher incidence of retinopathy of prematurity according to Del Rey Hurtado de Mendoza et al 4) Conversely, other studies reported that thrombocytopenia, not thrombocytosis, is a risk factor for retinopathy of prematurity. 34) Thus, the association between thrombocytosis and retinopathy of prematurity remains controversial.…”
Section: Complications Of Thrombocytosismentioning
confidence: 98%
“…Infectious pathogens and immune complexes formed by them can activate platelets, which then secrete molecules to activate immune reactions [ 23 ]. Thom et al [ 24 ] suggested that rebound vigorous multilineage hematopoiesis following myelosuppression due to critical illnesses such as infection, inflammation, or iron deficiency can lead to hyperactive bone marrow and result in thrombocytosis.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Moreover, many interleukins (IL) involved in the inflammation processes, mostly IL-6 and IL-11, can stimulate the platelet production in the liver [ 27 , 28 ]. These processes are highly active during childhood: ST is reported in 6–15% of hospitalized children, and up to 1% of children in intensive care units show platelet counts exceeding 1000 × 10 9 /L [ 5 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Reactive/secondary Thrombocytosis (St)mentioning
confidence: 99%
“…Infections, both bacterial and viral, are common causes of thrombocytosis in infants (75% of cases [ 31 ]), and children (47% [ 33 ]), mostly of the respiratory and urinary tracts. All other pediatric inflammatory conditions are associated with ST [ 34 ], in particular those seen in young children, such as Kawasaki disease [ 36 ], Schoenlein–Henoch syndrome, coeliac disease as well as rheumatic diseases and damages to tissues due to trauma, surgery or burns [ 8 ].…”
Section: Reactive/secondary Thrombocytosis (St)mentioning
confidence: 99%
See 1 more Smart Citation